Impact of comorbidity on the short- and medium-term risk of revision in total hip and knee arthroplasty - Jorge Arias-de la Torre; Kayla Smith; Alexandru Dregan; Jose M. Valderas; Jonathan P. Evans; Daniel Prieto-Alhambra; Luis Lozano; Antonio J. Molina; Vicente Martín; Laia Domingo; Laura Muñoz; Mireia Espallargues (BMC Musculoskeletal Disorders, 2020)
Abstract Background The impact of comorbidity on the risk of revision in patients undergoing Total Knee arthroplasty (TKA) and Total Hip Arthroplasty (THA) is not currently well known. The aim of this study was to analyze the impact of comorbidity on the risk of revision in TKA and THA. Methods Patients recorded in the Catalan Arthroplasty Register (RACat) between 01/01/2005 and 31/12/2016 undergoing TKA (n = 49,701) and THA (n = 17,923) caused by osteoarthritis were included. As main explanatory factors, comorbidity burden was assessed by the Elixhauser index, categorized, and specific comorbidities from the index were taken into account. Descriptive analyses for comorbidity burden and specific conditions were done. Additionally, incidence at 1 and 5 years’ follow-up was calculated, and adjusted Competing Risks models were fitted. Results A higher incidence of revision was observed when the number of comorbidities was high, both at 1 and 5 years for THA, but only at 1 year for TKA. Of the specific conditions, only obesity was related to the incidence of revision at 1 year in both joints, and at 5 years in TKA. The risk of revision was related to deficiency anemia and liver diseases in TKA, while in THA, it was related to peripheral vascular disorders, metastatic cancer and psychoses. Conclusions Different conditions, depending on the joint, might be related to higher revision rates. This information could be relevant for clinical decision-making, patient-specific information and improving the results of both TKA and THA.